PENYALAHGUNAAN HAK TANAH OLEH DEVELOPER DAN PERLINDUNGAN KONSUMEN PEMBELI PROPERTI - Berlian, Cheny; AKbar Santoso, Mulia; Aksar (UIR Press, 2025)
Abstract: The rapid property development in Indonesia is often followed by issues related to land rights abuse by developers, which harms consumers in property transactions. One of the main problems is the sale of land with unclear legal status or land under dispute, leading to the risk of consumers losing their property rights. This study aims to analyze the impact of land rights abuse by developers on consumer protection and the implementation of the Consumer Protection Law in improving dispute resolution mechanisms in cases of developer default. The study uses a normative legal research method with a descriptive-analytical approach, analyzing applicable regulations, legal principles, and relevant legal theories. Data was collected through library research using primary and secondary data sources and analyzed qualitatively. The results indicate that land rights abuse by developers significantly impacts consumers, both financially and psychologically. Developer defaults related to delays, discrepancies in property specifications, and land legal issues increase consumer distrust in the property sector. The implementation of the Consumer Protection Law through the Consumer Dispute Settlement Body (BPSK) can improve dispute resolution mechanisms, although challenges in consumer awareness and the enforcement of BPSK decisions still need to be addressed. Stronger law enforcement and improved transparency will enhance consumer protection. Keywords: Land Rights Abuse, Developer Default, Consumer Protection